(untitled) (International Journal of Engineering and Computer Science, 2015)
The present paper provides the conceptual framework of next three generation of wireless technologies: Wi-Fi, WiMAX and MBWA the formally, in which expertise or combination of two expertise provide a key for making of a wireless network. Every expertise are assessed founded on presentation, exposure zone, dependability.